ANALISIS PENGGUNAAN METODE MURDOCK DALAM PENGUKURAN LAJU ALIR DUA FASA DI LAPANGAN PANAS BUMI - PRABOWO , TEGUH
Flow Measuring is an important part in determining production capacity and electrical power which are generated from a well in geothermal field. Water-steam two-phase fluid flow is commonplace in a geothermal field, but no method which fits in measuring that kind of fluid using differential meters suh as orifice flowmeter, etc. Murdock has developed a method to measure gas-liquid two-phase flow with principle is that an orifice flowmeter coul be considered as a very rough pipe of short length, then the basic correlating parameters should be identical and only the numerical constants should be different. The object of this study is to analyze the application of tw-phase flow measurement developed by Murdock in a geothermal field by comparing the result of flow measurement from an two-phase geothermal well by orifice flowmeter and tracer flow test. The result from this study show that the result of two-phase measurements with orifice flowmeter generally almost give the same result compared with the result from tracer flow test. This means, we can conclude that mass flow measurement using orifice flowmeter based on ASME-Murdock method can be applicated to measure mass flow rate in a geothermal field as complemet with the result from tracer flow test, even though further study about this case wil give better result.